A green method for the preparation of Ag microparticles with tunable nanopores

CN119870485BActive Publication Date: 2026-10-09ZHEJIANG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510047493.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2026-10-09
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

然而,它需要大约1000℃的高温和长时间处理过程

Benefits of technology

[0020] (1) This invention uses a green reducing agent to electrodeposit pre-prepared torpedo-shaped Ag7O 11 The N superstructure is reduced in a conformal manner to Ag microparticles with bicontinuous nanopores. By controlling the concentration of the reducing agent and the reaction temperature, Ag7O is chemically removed. 11 The N and O elements in the N superstructure enable the programmable construction of Ag particles with different pore sizes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119870485B_ABST
    Figure CN119870485B_ABST
Patent Text Reader

Abstract

The application discloses a green preparation method of Ag microparticles with adjustable nanometer pores. 11 The N and O elements in the N superstructure are removed by chemical methods to form Ag microparticles with double-continuous nanometer pores. 11 The N and O elements in the N superstructure are removed by chemical methods to form Ag microparticles with double-continuous nanometer pores. The Ag microparticles with adjustable nanometer pores obtained by the method have the functions of enhanced SERS hot spots and analyte storage, and can be used as a substrate for surface enhanced Raman scattering and for detection of biological proteins such as AFP.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention pertains to electrochemical deposition and chemical reaction systems, specifically relating to Ag7O. 11 The preparation of N superstructure materials, particularly a green preparation method for Ag microparticles with tunable nanopores. Background Technology

[0002] Nanoporous metals with ultra-clean surfaces possess chemical reactivity, large surface areas, and interconnected nanostructures, making them promising candidates for applications in catalysis and sensing. Nature utilizes the self-assembly synergistic process of ions and biological species to form ordered microstructures, yielding nanoporous structures after the decomposition of perforating biological species. Similar to nature, organic micelles are used as perforating agents in the wet chemical growth of metals to prepare nanoporous metals. However, organic perforating agents are difficult to completely remove from the sidewalls of nanopores, significantly impacting catalytic and sensing performance. Dealloying processes can prepare surface-clean nanoporous metals by removing one component from a solid solution. However, this requires high temperatures of approximately 1000°C and long processing times. Furthermore, predicting and controlling the structure of nanopores using wet chemical or dealloying methods is challenging. Developing a method to fabricate clean nanoporous metals with strong structural control capabilities at room temperature and within minutes is imperative.

[0003] Surface-enhanced Raman scattering (SERS), a detection technique based on Raman scattering spectroscopy, can identify unknown molecular species through the characteristic "fingerprint signals" of molecules and has the ability to detect multiple molecules simultaneously. Furthermore, by designing ultrasensitive SERS substrates, researchers can even achieve single-molecule detection. Therefore, SERS as a sensing technology has broad application prospects in chemical analysis, biomedicine, environmental monitoring, and drug detection. Ultra-clean nanopores can not only provide sensitive SERS hotspots but also trap and enrich analyte molecules. Therefore, nanoporous Ag microstructures have shown outstanding SERS performance in detecting disease biomarkers. Summary of the Invention

[0004] The purpose of this invention is to address the shortcomings of existing technologies by electrodepositing Ag7O 11 The N superstructure was then chemically removed from Ag while maintaining its shape. Nanoporous Ag microparticles could be formed within minutes at room temperature without the use of any organic agents. Furthermore, based on the ion diffusion-limited growth mechanism, the relationship between the nanopore opening size and the reducing agent concentration was established, enabling the rational preparation of porous structures with opening sizes ranging from less than 30 nm to greater than 200 nm.

[0005] To achieve the above objectives, the technical solution provided by this invention is as follows:

[0006] In a first aspect, a green method for preparing Ag microparticles with tunable nanopores is provided, comprising the following steps: electrodeposition to prepare Ag7O 11 N-type superstructure, using green reducing agents to chemically remove Ag7O 11 The N and O elements in the N superstructure yield Ag microparticles with nanopores.

[0007] Furthermore, the green reducing agent used is NaBH4.

[0008] Furthermore, the chemical removal of Ag7O using a green reducing agent... 11 The N and O elements in the N superstructure are specifically: Ag7O 11 The N-type superstructure is immersed in a 5mM to 5M NaBH4 aqueous solution for reduction reaction, and the reaction temperature is maintained at 0℃ to 60℃. After the reaction is completed, Ag microparticles with continuous nanopores are obtained.

[0009] Specifically, the reduction reaction ends with the following phenomenon: Ag7O 11 The color of the N superstructure changed from black to gray and no bubbles were generated.

[0010] Furthermore, the Ag7O 11 The N-type superstructure material was prepared by the following method: using a three-electrode system, with a deionized aqueous solution of AgNO3 and H3BO3 as the electrolyte, Ag7O was electrodeposited on the working electrode using a gradually decreasing voltage mode. 11 N-type superstructure material. Then, using vibration or droplet rolling, the individually grown superstructure material is peeled off from the working electrode onto a clean silicon wafer for subsequent reduction reaction.

[0011] Specifically, in the electrolyte, the concentration of AgNO3 is 0.06M, the concentration of H3BO3 is 0.16M, the electrodeposition voltage gradually decreases from 10V to 2V, the voltage change rate is greater than or equal to 0.001V / s, and the temperature is room temperature.

[0012] Furthermore, by controlling the concentration of the reducing agent and the reaction temperature, Ag7O is chemically removed. 11 The N and O elements in the N superstructure enable the programmable construction of Ag particles with different pore sizes.

[0013] Specifically, when the concentration of the reducing agent is controlled to be less than 5 mM, the Ag microparticles obtained from the reaction have a maximum pore size greater than 200 nm; when the concentration of the reducing agent is controlled to be in the range of 5 mM to 500 mM, the average pore size of the particles obtained is less than 100 nm; when the concentration of the reducing agent is controlled to be in the range of 500 mM to 5 M, nanoporous Ag microparticles with a minimum pore size of less than 20 nm are obtained; when the concentration of the reducing agent is greater than 5 M, the surface of the Ag microparticles obtained from the reaction loses its porosity.

[0014] Specifically, within the temperature range of 0℃ to 60℃, temperature only affects the size of the grains obtained from the reaction, and its effect on the pore size is negligible.

[0015] Specifically, within the NaBH4 concentration range of 5 mM to 500 mM, a relationship between the nanopore opening size and the reducing agent concentration was established based on the ion diffusion-limited growth mechanism: Φ = -37.64Log C + 140.12, where C represents the NaBH4 concentration and Φ represents the nanopore diameter, thereby enabling the programmable construction of Ag particles with different pore sizes.

[0016] Secondly, a method for preparing nanoporous Ag microparticles as described above is provided.

[0017] Thirdly, the invention provides the use of the aforementioned nanoporous Ag microparticles in the preparation of SERS substrates.

[0018] Specifically, SERS substrates are prepared using 30nm nanoporous Ag microparticles for cancer detection.

[0019] Compared with the prior art, the beneficial effects of the present invention are reflected in:

[0020] (1) This invention uses a green reducing agent to electrodeposit pre-prepared torpedo-shaped Ag7O 11 The N superstructure is reduced in a conformal manner to Ag microparticles with bicontinuous nanopores. By controlling the concentration of the reducing agent and the reaction temperature, Ag7O is chemically removed. 11 The N and O elements in the N superstructure enable the programmable construction of Ag particles with different pore sizes.

[0021] (2) The present invention also uses the Ag microparticles with tunable nanopores obtained by the above method as a substrate for surface-enhanced Raman scattering and for the detection of disease biomarkers such as AFP, which is expected to be applied in the field of cancer detection. Attached Figure Description

[0022] Figure 1 Ag7O in Example 1 11 A schematic diagram of the fabrication process of N-type torpedo microparticles; where a is the potential curve for anodic electrodeposition in torpedoes; b is Ag7O11 Schematic diagram of the growth process of N-torpedo microparticles;

[0023] Figure 2 The figures show the characterization results of the microparticles before and after the conformal reduction process of the porous Ag torpedo in Example 2; where a and b are the electrodeposited Ag7O. 11 SEM and XRD images of N-type torpedo particles; c and d are images of particles composed of Ag7O. 11 SEM and XRD images of porous Ag particles obtained by reducing N particles;

[0024] Figure 3 Example 3 shows how the open size of the nanopores within the Ag particles is controlled by adjusting the concentration of the reducing agent; a is a schematic diagram showing the formation of nanoporous silver particles with different pore sizes by changing the concentration of the NaBH4 aqueous solution; be are scanning electron microscope images of nanoporous Ag particles prepared at NaBH4 concentrations of 5 mM, 50 mM, 500 mM, and 5 M, respectively; f is the size distribution diagram of the nanopores corresponding to bd; g is a linear relationship diagram between the nanopore size and the concentration of the sodium borohydride aqueous solution.

[0025] Figure 4 To illustrate the SERS performance of single-particle nanoporous Ag microparticles in Example 1; a) shows the SERS spectra of 1 μM R6G molecules detected using nanoporous Ag microparticles with different nanopore sizes; b and c) show the electromagnetic field distributions on 30 nm and 200 nm nanoporous Ag microparticles simulated using FDTD, respectively. The left image is the model image, and the right image is the simulation result. The strongest electromagnetic field appears at the edge of the pores marked by the green arrow; d) shows the SERS spectra of R6G molecules at different concentrations on nanoporous Ag microparticles; e) shows the SERS spectra of 610 cm⁻¹. -1 The relationship between SERS intensity and R6G concentration at a given location was established using error bars derived from five spectral curves; f represents the SERS mapping result of R6G molecules on nanoporous Ag particles, and the inset shows the optical image of the SERS mapping region; g represents 610 cm⁻¹. -1 Intensity statistics of SERS peaks obtained from 20 randomly selected positions on nanoporous Ag particles;

[0026] Figure 5 In Application Example 2, using nanoporous Ag particles as a substrate, reliable and sensitive SERS protein detection is achieved by unfolding the protein structure; a) is a schematic diagram of protein detection by unfolding the protein structure and exposing the hidden parts to the SERS substrate; b) shows the protein detection at a protein concentration of 1.05 μg / ml. -1Below is a comparison of the SERS spectra of normal and unfolded AFP protein, with newly appearing peaks marked by blue dashed lines; c and d are the SERS mapping images of unfolded and normal AFP protein on nanoporous Ag particles, respectively; e is the SERS spectrum of unfolded AFP protein on nanoporous Ag particles at different concentrations; f is the SERS spectrum at 655 cm⁻¹. -1 The relationship between the SERS intensity at a given location and the concentration of AFP protein during unfolding was established, and error bars were obtained based on five spectra; g represents a comparison of the SERS spectra of CA125 and CA15-3 proteins before and after protein structure unfolding.

[0027] Figure 6 In Application Example 3, nanoporous Ag microparticles were used as SERS substrates for liver cancer diagnosis; a) Normalized mean SERS spectra of serum samples from 25 liver cancer patients (HCC) and 25 normal individuals (Normal), with the shaded area representing the mean standard deviation; b) Histograms of the mean intensity and standard deviation of SERS peaks in the HCC and normal groups (*p<0.05); c) Two-dimensional PCA-LDA scores; d) Groups generated from the ROC classification results of PCA and LDA analyses (AUC: area under the ROC curve). Detailed Implementation

[0028] Example 1 Ag7O 11 Preparation of N superstructures.

[0029] (1) Take a silicon wafer and place it in a vapor deposition apparatus. The first layer is a 10nm titanium layer as a buffer layer, and the second layer is a 50nm gold layer. The deposition rate is maintained at 0.1nm / s. Cut the deposited silicon wafer into 1cm×2cm pieces to obtain the working electrodes. The obtained working electrodes are ultrasonically cleaned in ethanol and deionized water for 10min each.

[0030] (2) Dissolve AgNO3 and H3BO3 in 50 ml of deionized water to obtain an electrolyte with a final concentration of AgNO3 of 0.06 M and a final concentration of H3BO3 of 0.16 M.

[0031] (3) In the three-electrode system, the electrode prepared in (1) is used as the working electrode, a carbon rod with a diameter of 2 mm is used as the counter electrode, and Ag / AgCl is used as the reference electrode. The distance between the working electrode and the counter electrode is maintained at 4 cm. Figure 1 As shown in b. The electrodeposition temperature was maintained at 25℃, which is room temperature. In the three-electrode system, a voltage mode with gradually decreasing voltage was selected for electrodeposition, with the parameters set as follows: high voltage 10V, low voltage 2V, and scan rate 0.2V / s. Figure 1 As shown in a.

[0032] The Ag7O obtained by electrodeposition using the gradually decreasing voltage electrodeposition mode11 N-type superstructure materials such as Figure 2 As shown in Figure a, it is a columnar structure with one end being a pointed tip and the other end being a thicker tip. The surface of the columnar structure has centrally symmetrically distributed indentations, and the overall shape is streamlined, similar to a torpedo. Figure 2 The XRD results of b show that the composition of the obtained torpedo is Ag7O. 11 N.

[0033] Example 2: Preparation of porous Ag structure.

[0034] Ag7O was prepared in Example 1. 11 After N-type superstructure, a layer of gray-black powder is applied to the surface of the gold electrode. The prepared anode electrode is then slowly immersed in deionized water at an angle of approximately 30° to peel off Ag7O from the electrode surface. 11 N-type micro-torpedoes. The detached micro-torpedoes were transferred onto a silicon wafer and reacted in a NaBH4 aqueous solution for 10 minutes. The reaction was complete when the color of the micro-torpedoes changed from black to gray and no more bubbles were produced. After the reduction reaction, the porous Ag micro-torpedoes were transferred to a clean silicon wafer surface for subsequent use. Scanning electron micrographs of the micro-torpedoes are shown below. Figure 2 As shown in c. Figure 2 The XRD results of d showed that the porous torpedo obtained by the reduction reaction was composed of Ag.

[0035] Example 3: Preparation of Ag microparticles with different pore structures.

[0036] The size of the nanopores depends on the supply rate of Ag atoms and Ag7O. 11 The competition between the etching rates of N and NaBH4 is determined by the reaction kinetics, which are controlled by the NaBH4 solution concentration. When the silver atom supply rate is low, the growth rate of the nanopore walls should be slow, resulting in large nanopores. As the silver atom supply rate increases, the size of the nanopores gradually decreases. Schematic diagrams of porous silver obtained from the reaction with NaBH4 solutions of different concentrations are shown below. Figure 3 As shown in a.

[0037] As expected, when the NaBH4 concentration increased from 5 mM to 50 mM, the average size of the nanopores decreased from ~110 nm to ~80 nm. Figure 3 As shown in b and 3c. When the concentration increases to 500 mM, the pore size further decreases to ~40 nm, as... Figure 3 As shown in d, when the concentration of NaBH4 increases to 5M, the nanopores disappear, as... Figure 3 As shown in e. Figure 3 f is the size distribution diagram of the nanopores corresponding to 3b-d. For example... Figure 3 As shown in g, the relationship between the size of the nanopores and the concentration of NaBH4 can be described by Φ = -37.64LogC + 140.12, R2 The value is 0.992, where C represents the concentration of NaBH4 and Φ represents the diameter of the nanopores.

[0038] Application Example 1: SERS detection effect of porous Ag.

[0039] To investigate the effect of porous structure size on SERS performance, we compared the SERS detection performance of porous Ag particles (without nanopores, with an average pore size of 30 nm, and with an average pore size of 110 nm) obtained in Example 3. Using Rhodamine 6G (R6G) as the probe molecule, the obtained SERS peak intensities were as follows: Figure 4 As shown in Figure a, silver nanoparticles without pores exhibit a weak R6G SERS signal. Ag nanoporous particles with an average pore size of 110 nm exhibit a slightly stronger SERS signal. Ag nanoporous particles with an average pore size of 30 nm exhibit the strongest SERS signal. The enhancement of the electromagnetic field signal of the nanopores obtained by FDTD simulation is shown in Figure a. Figure 4 As shown in b and c, torpedoes with 30 nm and 110 nm pores exhibit electromagnetic field enhancements of the same order of magnitude, located at the edges of the nanopores. However, the hotspot density of the 30 nm porous Ag particles is greater than that of the 110 nm porous Ag particles.

[0040] We evaluated the limit of detection (LOD) by immersing 30 nm porous Ag particles in R6G aqueous solutions of different concentrations for 2 hours. Figure 4 As shown in d, its detection limit can easily reach 1 pM. The concentration of R6G aqueous solution is similar to that at 610 cm⁻¹. -1 The relationship between the SERS peak intensities can be described by Log C = 5.28Log I - 27.85, as follows: Figure 4 As shown in e, the SERS mapping image reveals the uniformity of color in individual porous Ag particles, reflecting the uniformity of SERS enhancement in individual particles, as... Figure 4 As shown in f. The intensity distribution of the peak was calculated at 20 random points, 610 cm⁻¹. -1 The relative standard deviation (RSD) of the SERS peak at this location was only 5.2%, indicating the significant SERS detection reliability of porous Ag particles with a pore size of 30 nm. Figure 4 As shown in g.

[0041] Application Example 2: Protein Detection.

[0042] Here, we use porous Ag torpedo particles with an average pore size of 30 nm obtained in Example 3 as a single-particle SERS substrate for label-free SERS detection of proteins. Due to the large size and complex composition of proteins, detecting the SERS signal of components surrounded by other parts is challenging. To reliably collect the entire SERS signal of a protein, an effective method is to disassemble the spherical protein into unfolded proteins, such as… Figure 5 As shown in Figure a. Using alpha-fetoprotein (AFP) as a model protein, we obtained a stable unfolded protein by cleaving disulfide bonds and using stabilizers (such as urea) to maintain its unfolded state, as shown in Figure a. Figure 5 As shown in step two of section a. Unfolded proteins contain a large number of free sulfhydryl groups, which can promote the capture of target proteins by nanoporous Ag particles, such as... Figure 5 As shown in step 3 of section a.

[0043] Dilute 30 μL of AFP solution (1.05 μg / mL) into 3 mL of aqueous solution. Then, add 50 μL of disulfide reducing agent (tris(2-carboxyethyl)phosphine, TCEP, 0.01 mM) and 100 μL of stabilizer (urea, 0.5 mM). After standing at room temperature for 4 h, an unfolded protein dispersion is obtained. Then, porous Ag microparticles are immersed in it for 2 h. Figure 5 As shown in b, the SERS signal observed from the unfolded AFP is much stronger than that from the spherical AFP. More importantly, a new, previously hidden SERS peak was collected from the unfolded AFP. Furthermore, at 1246 cm⁻¹... -1 The increase in SERS peak intensity and 1280 cm⁻¹ -1 The decrease in SERS peak intensity confirms the protein's transition from α-helix to β-sheet.

[0044] like Figure 5 As shown in c, the SERS-mapped image of the folded AFP has uniform color, 655cm. -1 The RSD of the SERS peak was only 7.2%, indicating that the detection of unfolded proteins using our nanoporous Ag microparticle SERS substrate has significant reliability. In contrast, the SERS mapping results showed that the SERS intensity of spherical AFPs fluctuated significantly, with an RSD reaching 43.9%. Figure 5 d).

[0045] like Figure 5 As shown in Figure e, we further evaluated the LOD of the unfolded AFP protein on the substrate. Even at 10 ng / mL... -1 Even then, there was still a noticeable SERS peak, lower than the human body's 25 ng / mL level. -1 The normal value. For example... Figure 5 As shown in f, 655cm -1The relationship between the intensity of the SERS peak and the concentration of unfolded AFP can be described by Log C = 1.74Log I - 3.7, where R 2 The value was 0.998. Similarly, the unfolded CA125 and CA15-3 cancer biomarkers showed a stronger SERS signal than their globular-like proteins. Figure 5 These results demonstrate that protein unfolding is an effective method for enhancing SERS intensity and collecting the entire SERS signal from proteins, thereby improving the reliability of protein detection.

[0046] Application Example 3: Serum liver cancer detection.

[0047] To explore the application of nanoporous Ag microparticle SERS substrates in cancer diagnosis, we collected and normalized the serum SERS profiles of 25 normal individuals (N) and 25 patients with hepatocellular carcinoma (HCC). Figure 6 a) Various biological components in serum samples, such as lipids, proteins, and nucleic acids, can affect the intensity of SERS signals. Therefore, intensity analysis of SERS peaks can help explain the changes in serum composition observed in different serum groups.

[0048] The statistical intensity differences of the selected SERS peaks are as follows Figure 6 As shown in b. A univariate t-test was used to determine the peak indicating a significant difference between the healthy group and the cancer group, with a p-value <0.05. The HCC serum group peaked at 1003 cm⁻¹. -1 / 1576cm -1 (Phenylalanine), 1207cm -1 (tryptophan) and 1326cm -1 / 1447cm -1 The mean normalized intensity at (collagen, phospholipids) was higher in the normal serum group than in the healthy serum group. In contrast, the normal serum group showed a lower mean normalized intensity at 636 cm⁻¹. -1 (l-tyrosine), 723cm -1 (hypoxanthine), 810cm -1 (Low serine), 888cm -1 (d-galactosamine) and 1134cm -1 The SERS intensity at (D-mannose) was higher than that in the HCC serum group. We used Python tools to perform principal component analysis (PCA) and linear discriminant analysis (LDA) on the SERS profile to distinguish the SERS profiles in HCC and healthy individuals. The f1 and f2 values ​​obtained from LDA could completely distinguish between HCC patients and normal individuals. Figure 6 c). Subjects for whom operational characteristic curves were generated to further evaluate the performance of the LDA algorithm in cancer diagnosis. Figure 6d). The area under the curve (AUC) shows the predictive accuracy of each combined classification for the classifier performance. The AUC values ​​calculated by PCA and LDA are 0.92 and 1.00, respectively. Therefore, the diagnostic results analyzed using the LDA algorithm are suitable for the diagnosis of HCC based on serum SERS profiles.

Claims

1. A green preparation method for Ag microparticles with tunable nanopores, characterized in that, The process includes the following steps: preparing Ag7O by electrodeposition. 11 N-type superstructure, using green reducing agents to chemically remove Ag7O 11 The N and O elements in the N superstructure are used to obtain Ag microparticles with nanopores; the Ag7O is chemically removed using a green reducing agent. 11 The N and O elements in the N superstructure are specifically: Ag7O 11 The N-type superstructure was immersed in a 5 mM ~ 5 M NaBH4 aqueous solution for reduction reaction, and the reaction temperature was maintained at 0℃ ~ 60℃. After the reaction was completed, Ag microparticles with continuous nanopores were obtained. The Ag7O 11 The N-type superstructure material was prepared by the following method: using a three-electrode system, with a deionized aqueous solution of AgNO3 and H3BO3 as the electrolyte, Ag7O was electrodeposited on the working electrode using a gradually decreasing voltage mode. 11 N-type superstructure materials; Individual, fully grown superstructure materials are peeled from the working electrode onto a clean silicon wafer using vibration or droplet rolling methods for subsequent reduction reactions; By controlling the concentration of the reducing agent, Ag microparticles with nanopores of different pore sizes can be programmably constructed. Specifically, the concentration of the reducing agent is controlled between 5 mM and 500 mM to prepare Ag microparticles with nanopores of average pore size less than 100 nm; the concentration of the reducing agent is controlled between 500 mM and 5 M to prepare Ag microparticles with nanopores of minimum pore size less than 20 nm. The reduction reaction ends with the following phenomenon: Ag7O 11 The color of the N-superstructure changed from black to gray and no bubbles were generated; When the concentration of NaBH4 is in the range of 5 mM to 500 mM, Ag microparticles with nanopores of different pore sizes are constructed by the following relationship between the size of the nanopores and the concentration of NaBH4: Φ = -37.64 Log C + 140.12, where C represents the concentration of NaBH4 and Φ represents the diameter of the nanopores.

2. The preparation method according to claim 1, characterized in that, The electrolyte contains 0.06 M AgNO3 and 0.16 M H3BO3. The electrodeposition voltage gradually decreases from 10 V to 2 V, with a voltage change rate greater than or equal to 0.001 V / s, and the temperature is room temperature.

3. A nanoporous Ag microparticle prepared by the preparation method of claim 1.

4. The use of the nanoporous Ag microparticles of claim 3 in the preparation of SERS substrates, characterized in that, The application described uses Ag microparticles with 30 nm nanopores to prepare SERS substrates for cancer detection.

Citation Information

Patent Citations

  • Application of chemical self-driven microrobot in biological sterilization

    CN113797227A